The Administration of Halalan Tayyiban Products and Services in the Era of Islamic Caliphates under Hisbah Institution - Haqqi, Abdurrahman Raden Aji (University of Darusssalam Gontor, 2017)
A caliphate is a territory under the leadership of an Islamic steward known as acaliph, a person considered a religious successor to the Muhammad and a leader of theentire Muslim community. Historically, the caliphates were polities based in Islam whichdeveloped into multi-ethnic trans-national empires. During the medieval period, threemajor caliphates existed: the Rashidun Caliphate (632–661), the UmayyadCaliphate (661–750) and the Abbasid Caliphate (750–1258). The fourth major caliphate,the Ottoman Caliphate, established by the Ottoman Empire in 1517. One of the dutiesof a caliph is to administer and control the market which was included in Hisbah system.The Hisbah is a religious institution under the authority of the state that appointspeople to carry out the responsibility of enjoining what is right, whenever people start toneglect it, and forbidding what is wrong, whenever people start to engage in it. Thepurpose of this is to safeguard society from deviance, protect the faith, and ensure thewelfare of the people in both religious and worldly manners according to the Law ofAllah. Allah has made it obligatory upon all Muslims to enjoin good and forbid wrongdoingto the extent of their knowledge and abilities. Halalan Tayyiban products and serviceswere controlled under this institution. And this paper is an attempt to highlight suchcontrol in the history of Islam. How were Halalan Tayyiban products and servicesadministered and controlled?